HERMENEUTIKA DIALEKTIS OTENTISITAS HADIS: REKONSTRUKSI EPISTEMOLOGI INTEGRATIF JOSEPH SCHACHT DAN MUḤAMMAD MUṢṬAFĀ AL-A‘ẒAMĪ - Zira Shafira; Hifsa Nurrahim; Uli Nashrul Lathifi; Syahru Nur Zaman; M. Rajib Habiburrahman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
The debate on the authenticity of hadith between Joseph Schacht and Muḥammad Muṣṭafā al-A‘ẓamī represents a fundamental friction between Western historical-critical approaches and traditional Islamic internal authentication. This study aims to analytically explore the philosophical foundations, methodological convergences, and divergences of both scholars. Employing library research and content analysis, this study adopts Paul Ricoeur’s dialectical hermenutics framework, which juxtaposes the hermeneutics of suspicion and the hermeneutics of faith. The results indicate that Schacht’s paradigm functions as a hermeneutics of suspicion through deconstructive instruments such as back-projection and argumentum e silentio. Conversely, al-A‘ẓamī’s methodology embodies a hermeneutics of faith that restores textual authority through internal transmission devices (isnād cum matn) and first-century AH documentary evidence. The novelty of this study lies in its synthesis of an integrative isnād-historical epistemological model that reconfigures Western critical analysis as an external control mechanism, while preserving the traditional isnād coherence as the primary internal control core. This study implies that the integrative model serves as a robust framework for epistemic decolonization in contemporary Islamic studies and offers a layered verification mechanism to address information validity crises in the digital era.